2021
DOI: 10.3390/cancers13061295
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Safety and Efficacy of Microwave Ablation Using ThermosphereTM Technology versus Radiofrequency Ablation for Hepatocellular Carcinoma: A Propensity Score-Matched Analysis

Abstract: There is limited information regarding the oncological benefits of microwave ablation using ThermosphereTM technology for hepatocellular carcinoma. This study compared the overall survival and recurrence-free survival outcomes among patients with hepatocellular carcinoma after microwave ablation using ThermosphereTM technology and after radiofrequency ablation. Between December 2017 and August 2020, 410 patients with hepatocellular carcinoma (a single lesion that was ≤5 cm or ≤3 lesions that were ≤3 cm) underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A key element in MWA treatments is the microwave antenna (MW), which delivers energy and provides lethal temperature rise, resulting in cell death in the ablation zone [ 36 ]. Advanced antenna designs are based on three different mechanisms: thermal, field, and wavelength control [ 37 ]. Recently, a compact, multi-slot coaxial antenna was developed to achieve the required ablation zone and suitable impedance matching to the target tumoral tissue without damaging the surrounding healthy tissues [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A key element in MWA treatments is the microwave antenna (MW), which delivers energy and provides lethal temperature rise, resulting in cell death in the ablation zone [ 36 ]. Advanced antenna designs are based on three different mechanisms: thermal, field, and wavelength control [ 37 ]. Recently, a compact, multi-slot coaxial antenna was developed to achieve the required ablation zone and suitable impedance matching to the target tumoral tissue without damaging the surrounding healthy tissues [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finely tuned impedance matching minimizes damage to the surrounding healthy tissues. In one of the most sophisticated antenna designs, the required ablation zones are achieved using three different mechanisms: Thermal, field, and wavelength controls [ 32 , 33 ].…”
Section: Modeling Of the Electromagnetic Field Generated By The Antennamentioning
confidence: 99%
“…[ 30 , 31 ]. Some commercial MWA systems based on “thermosphere technology” can produce spherical ablation patterns by adding small saline irrigation channels to the antennas [ 32 , 33 ]. Novel compact multislot coaxial antennas ensure the formation of spherical ablation zones that are suitable for the interstitial MWA process [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the comparison should have been performed after matching of important characteristics. Interestingly, a similar study that was based on a propensity score-matched analysis found no significant differences in recurrence free survival and overall survival between the Emprint ablation system and RFA for small HCC 2 .…”
mentioning
confidence: 93%